Complete Coverage Path Planning for a Multi-UAV Response System in Post-Earthquake Assessment - Nedjati, Arman; Izbirak, Gokhan; Vizvari, Bela; Arkat, Jamal (Mdpi, 2016)
This paper presents a post-earthquake response system for a rapid damage assessment. In this system, multiple Unmanned Aerial Vehicles (UAVs) are deployed to collect the images from the earthquake site and create a response map for extracting useful information. It is an extension of well-known coverage path problem (CPP) that is based on the grid pattern map decomposition. In addition to some linear strengthening techniques, two mathematic formulations, 4-index and 5-index models, are proposed in the approach and coded in GAMS (Cplex solver). They are tested on a number of problems and the results show that the 5-index model outperforms the 4-index model. Moreover, the proposed system could be significantly improved by the solver-generated cuts, additional constraints, and the variable branching priority extensions.
Keywords: coverage path planning; rapid damage assessment; UAV monitoring; post-earthquake response